Evidence to act: LGBTIQ-inclusive family violence service provision in Australia and the politicisation of data gaps - Lusby, Stephanie (Journal of family violence, 2024)
Purpose: There are inadequate resources available to support lesbian, gay, bi + , trans and gender diverse, intersex and queer (LGBTIQ) people experiencing family violence in Australia. Government funding agencies and mainstream family violence service providers regularly state that there is insufficient evidence to justify investment in more inclusive services. This article explores practitioner perceptions of such claims. Method: 21 practitioners from mainstream and specialist LGBTIQ family violence services were interviewed about structural challenges associated with implementing LGBTIQ-inclusive family violence services. Participants’ accounts highlight the political tensions and material repercussions of epistemic definitions of ‘evidence’ as they pertain to LGBTIQ individuals’ experiences of violence within policy environments. Utilizing Carol Bacchi’s feminist policy analysis framework, we ask ‘what is the problem represented to be?’, examining participant perceptions about how evidence is currently positioned in policy and resourcing decisions pertaining to LGBTIQ family violence, and discuss its implications. Results: Participants overwhelmingly called for more investment in research and data gathering about family violence against LGBTIQ people and provision of effective supports. Even allowing for this, participants indicated that there is also already enough existing knowledge to justify urgent expansion of LGBTIQ-inclusive services. Conclusions: Expanded provision of services and generating a more robust evidence base about LGBTIQ family violence service needs are critically important and intertwined issues. However, the way that they are currently sequenced in policy and broader sector conversations, where ‘enough’ evidence is required in order to justify increased services, is inhibiting progress on both.